2017
DOI: 10.4274/tjo.89577
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Corneal Densitometry in Rheumatoid Arthritis Patients

Abstract: Objectives:To evaluate corneal densitometry and anterior segment parameters of rheumatoid arthritis (RA) patients and compare these results with those of age-matched healthy control subjects.Materials and Methods:Anterior segment parameters and corneal densitometry of patients with RA and healthy control subjects were assessed by Scheimpflug corneal topography. For densitometry analysis, the 12-mm diameter area of the cornea was subdivided into four concentric radial zones and anterior, central, and posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…In previous studies, HM eyes were reported to have different cornea-related parameters, such as corneal curvature, corneal thickness, corneal endothelial density, corneal hysteresis, and corneal resistance factor, compared with normal eyes [ 4 , 5 , 8 , 16 19 ]. Clinical analysis of corneal light backscatter played an important role in the evaluation of the corneal status and in monitoring the progression of some corneal diseases [ 11 15 ]. In our study, we found a decrease in light backscatter in the central cornea (10 mm in diameter) and total diameter in the HM group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, HM eyes were reported to have different cornea-related parameters, such as corneal curvature, corneal thickness, corneal endothelial density, corneal hysteresis, and corneal resistance factor, compared with normal eyes [ 4 , 5 , 8 , 16 19 ]. Clinical analysis of corneal light backscatter played an important role in the evaluation of the corneal status and in monitoring the progression of some corneal diseases [ 11 15 ]. In our study, we found a decrease in light backscatter in the central cornea (10 mm in diameter) and total diameter in the HM group.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal densitometry, as an indicator for corneal health, has many applications in corneal diagnosis, such as the diagnosis of bacterial keratitis, keratoconus, pseudoexfoliation syndrome, Fuchs endothelial dystrophy, and rheumatoid arthritis, etc. [ 11 15 ] The use of this technique to assess corneal transparency in HM patients has not been reported before, and this technique may provide some useful information when assessing the corneal clarity of HM eyes. The aim of this study was to perform corneal densitometry of normal and HM corneas, to investigate the imaging capabilities of Pentacam in patients with HM and the potential differences in corneal densitometry values between normal and HM eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Significant CD changes were seen 1 month onwards after PCRIs compared to 3 month onwards in tIOL group. CD has been studied on patients with general systemic diseases such as type 1 diabetes mellitus [13] and rheumatoid arthritis [14] as well as in some ocular conditions like bacterial keratitis [4], Fuchs' endothelial dystrophy [15] and keratoconus [16]. The changes in CD can occur due to various corneal refractive surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal and lens densitometry became popular in recent years to evaluate corneal health in various ocular and systemic disorders. Subclinical corneal and lens densitometry changes were detected in cases with type one-type two diabetes mellitus, rheumatoid arthritis, and Wilson disease [16][17][18][19]. A recently published report about corneal clarity changes in VKC patients showed increased corneal, and lens densitometry in VKC cases as the disease's clinical-grade severity worsens [20].…”
Section: Introductionmentioning
confidence: 99%